2006
DOI: 10.1002/bies.20384
|View full text |Cite
|
Sign up to set email alerts
|

Cell cycle control by oscillating regulatory proteins in Caulobacter crescentus

Abstract: Significant strides have been made in recent years towards understanding the molecular basis of cell cycle progression in the model bacterium Caulobacter crescentus. At the heart of cell cycle regulation is a multicomponent transcriptional feedback loop, governing the production of successive regulatory waves or pulses of at least three master regulatory proteins. These oscillating master regulators direct the execution of phase-specific events and, importantly, through intrinsic genetic switches not only dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 34 publications
1
22
0
4
Order By: Relevance
“…2A and B). Because the length of the cell cycle varies among growing cells (even within the same agarose-padded slide), it remained unclear if delocalization preceded or followed cytokinesis (i.e., the cytoplasmic compartmentalization of the predivisional cell), a key cell cycle event that determines the fate of daughter cells (2,5,7,16,20,42). Cytokinesis triggers many changes in the cell, including the release of DivK from the new pole into the swarmer cell compartment, while DivK remains localized at the old pole in the stalked cell compartment (27,37).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2A and B). Because the length of the cell cycle varies among growing cells (even within the same agarose-padded slide), it remained unclear if delocalization preceded or followed cytokinesis (i.e., the cytoplasmic compartmentalization of the predivisional cell), a key cell cycle event that determines the fate of daughter cells (2,5,7,16,20,42). Cytokinesis triggers many changes in the cell, including the release of DivK from the new pole into the swarmer cell compartment, while DivK remains localized at the old pole in the stalked cell compartment (27,37).…”
Section: Resultsmentioning
confidence: 99%
“…The alphaproteobacterium Caulobacter crescentus provides a model system that has been particularly useful for unraveling the bacterial cell cycle (2,5,7,16,20,42). Its life cycle is characterized by an asymmetric cell division that yields two distinct daughter cells, the motile swarmer cell and the sessile stalked cell.…”
mentioning
confidence: 99%
“…In addition, they regulate each other's transcription to create a cell cycle oscillator (reviewed in ref. 28).…”
Section: Just In Time Transcription and Transcription Network Oscillamentioning
confidence: 99%
“…Asynchronously growing cells can display different phenotypes depending on the stage of the cell cycle or the growth. Cell cycle-related variation plays an important role in the coordinate expression of genes required for replication and cell division (Holtzendorff et al 2006;Avery 2006), and has been shown to be responsible for the heterogeneous expression of certain proteins (Sumner and Avery 2002;Rosenfeld et al 2005). Biological cycles also occur on a longer time scale, as in circadian rhythms (Williams 2007).…”
Section: Sources Of Phenotypic Variationmentioning
confidence: 99%
“…In addition, a combination of a positive and a negative interaction is capable of inducing rhythmic oscillations. This type of regulation is a key component of both cell cycle regulation and circadian rhythms (Holtzendorff et al 2006;Williams 2007). Finally, it was shown that a three-component negative feedback loop (repressilator) can also cause oscillatory behavior (Elowitz and Leibler 2000).…”
Section: Bistability In Gene Expressionmentioning
confidence: 99%